( x 3 − 1 2 x 2 − x + 1 3 3 ) ( x 2 − 6 x − 5 5 ) = 1
Find the sum of all values of x satisfying the equation above.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Perfect solution
The L H S = 1 when:
{ x 3 − 1 2 x 2 − x + 1 3 3 = 1 x 2 − 6 x − 5 5 = 0 . . . ( 1 ) . . . ( 2 )
( 1 ) : x 3 − 1 2 x 2 − x + 1 3 2 ( x − 1 1 ) ( x 2 − x − 1 2 ) ( x − 1 1 ) ( x + 3 ) ( x − 4 ) ⇒ x = 0 By rational root theorem, we find that 11 is a root = 0 = 0 = ⎩ ⎪ ⎨ ⎪ ⎧ − 3 4 1 1
( 2 ) : x 2 − 6 x − 5 5 ( x + 5 ) ( x − 1 1 ) ⇒ x = 0 = 0 = { − 5 1 1
Therefore, there are 4 distinct solutions and their sum = − 5 − 3 + 4 + 1 1 = 7
Nice solution
Log in to reply
The answer will be 18 if we add 11 twice.
Log in to reply
You didn't mention in the QUESTION that we have to add only distinct roots.
Log in to reply
@Atanu Ghosh – "Sum of all values of x satisfying..." and they are − 5 , − 3 , 4 , 1 1 . It is not sum of all roots.
Log in to reply
@Chew-Seong Cheong – Okay Sir, thankz Now i understood.
Log in to reply
@Atanu Ghosh – Sir i have put some discussion on my profile as notes. Please check it out.
Problem Loading...
Note Loading...
Set Loading...
Let A = x 3 − 1 2 x 2 − x + 1 3 3 and B = x 2 − 6 x − 5 5 , then we have the equation A B = 1 . So all of the solutions to this equations must satisfy at least one of the following cases:
Case one : A = 1 .
Case two : B = 0 but A = 0 .
Case three : A = − 1 , and B is an even number.
For case one :, we have
x 3 − 1 2 x 2 − x + 1 3 3 = 1 ⇒ x 3 − 1 2 x 2 − x + 1 3 2 = 0
By rational root theorem , a possible root of the cubic equation above is ± factors of 132 . Trial and error shows that x = − 3 is a possible solution. By performing long division of polynomials, we have
x 3 − 1 2 x 2 − x + 1 3 2 = ( x + 3 ) ( x 2 − 1 5 x + 4 4 ) = ( x + 3 ) ( x − 1 1 ) ( x − 4 ) = 0 .
Thus the roots are x = − 3 , 1 1 , 4 . Substituting each of these values individually shows that all these 3 values are possible solutions.
For case two :, we have x 2 − 6 x − 5 5 = 0 ⇒ ( x + 5 ) ( x − 1 1 ) = 0 ⇒ x = − 5 , 1 1 .
Substituting each of these values individually shows that these 2 values are possible solutions as well.
For case three , we have x 3 − 1 2 x 2 − x + 1 3 3 = − 1 ⇒ x 3 − 1 2 x 2 − x + 1 3 4 = 0 . Rational root theorem shows that there is no integer solution of x , thus it is impossible for any of 3 roots of this cubic equation to satisfy the equation x 2 − 6 x − 5 5 = some even number .
In other words, there is no solution for case three.
Hence, gathering all the solutions from cases one to three, we have x = − 3 , − 5 , 4 , 1 1 , and their sum is − 3 − 5 + 4 + 1 1 = 7 .